Successful reintroduction of methotrexate after pneumonitis in two patients with rheumatoid arthritis. Issue 2 (February 1992) - Cook, N J; Carroll, G J
Abstract : Two patients are described with severe and progressive rheumatoid arthritis in whom methotrexate was reintroduced despite previous methotrexate related pneumonitis. In both patients a marked improvement in disease control occurred without a recurrence of the pneumonitis.